(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article presents Modular Dental Solution (MDS) - a comprehensive new generation technology designed for digital design and production of dental structures of varying complexity. MDR combines physical and digital systems, ensuring individualization, high accuracy, optimization, and automation of processes, as well as the ability to use data multiple times without repeated scanning. The physical part of MDR - Modular Dental Anatomical System (MDAS) - includes a frame module made of titanium or cobalt chromium using the selective laser alloying method (SLM) and an external anatomical module printed from a hybrid Cerasmart (GC) nanoceramic material on a component BD printer. The design ensures high strength, wear resistance, thermal stability, minimal tooth preparation, and the ability to be installed even with minimal number of support teeth. Digital Part - Modular Dental Digital System (MDSS) - includes a web platform for downloading STL scanners and managing orders, as well as an artificial intelligence system for automated module design and file preparation for printing. Training AI in one type of design increases the accuracy of model generation. The presented technology opens up new possibilities for clinical practice by reducing production time, improving the quality of structures, and simplifying repeated prosthetics without repeated diagnostics.